Low‐Threshold Lasing from Copper‐Doped CdSe Colloidal Quantum Wells. Issue 6 (4th May 2021) - Yu, Junhong; Sharma, Manoj; Li, Mingjie; Delikanli, Savas; Sharma, Ashma; Taimoor, Muhammad; Altintas, Yemliha; McBride, James R.; Kusserow, Thomas; Sum, Tze‐Chien; Demir, Hilmi Volkan; Dang, Cuong
Abstract: Transition metal doped colloidal nanomaterials (TMDCNMs) have recently attracted attention as promising nano‐emitters due to dopant‐induced properties. However, despite ample investigations on the steady‐state and dynamic spectroscopy of TMDCNMs, experimental understandings of their performance in stimulated emission regimes are still elusive. Here, the optical gain properties of copper‐doped CdSe colloidal quantum wells (CQWs) are systemically studied with a wide range of dopant concentration for the first time. This work demonstrates that the amplified spontaneous emission (ASE) threshold in copper‐doped CQWs is a competing result between the biexciton formation, which is preferred to achieve population inversion, and the hole trapping which stymies the population inversion. An optimum amount of copper dopants enables the lowest ASE threshold of ≈7 µJ cm −2, about 8‐fold reduction from that in undoped CQWs (≈58 µJ cm −2 ) under sub‐nanosecond pulse excitation. Finally, a copper‐doped CQW film embedded in a vertical cavity surface‐emitting laser (VCSEL) structure yields an ultralow lasing threshold of 4.1 µJ cm −2 . Exploiting optical gain from TMDCNMs may help to further boost the performance of colloidal‐based lasers. Abstract : The optical gain behavior in copper‐doped CdSe CQWs is the result of a competition between two opposite effects: biexciton formation, which facilitates the population inversion and hole trapping, which hinders the population inversion. By choosing an optimized doping level, an ultralow amplified spontaneous emission (ASE) threshold (≈7 µJ cm −2 ) and the single‐mode lasing have been demonstrated.